Oriented Molecular Attachments Through Sol–Gel Chemistry for Synthesis of Ultrathin Hydrated Vanadium Pentoxide Nanosheets and Their Applications. Issue 5 (14th November 2012) - Rui, Xianhong; Lu, Ziyang; Yin, Zongyou; Sim, Dao Hao; Xiao, Ni; Lim, Tuti Mariana; Hng, Huey Hoon; Zhang, Hua; Yan, Qingyu
<x xml:space="preserve">Abstract</x> Ultrathin single‐crystalline V2O5·0.76H2O nanosheets with a thickness of 1.5–2.6 nm are prepared on the basis of molecular‐level 'oriented attachment' through special sol–gel chemistry. The initial formation of 3–7 nm nanodiscs by confining the condensation reactions within the ab plane is critical to form nanosheets. As a proof‐of‐concept, these nanosheets exhibit good properties for hydrogen sensors and supercapacitors. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>